High quality linked data for stroke obtained using non-government clinical registry and routinely collected hospital and death data. (2018) - Kilkenny, Monique; Kim, Joosup; Andrew, Nadine; Sundararajan, Vijaya; Thrift, Amanda; Katzenellenbogen, Judith; Flack, Felicity; Gattellari, Melina; Boyd, James; Anderson, Phil; Lannin, Natasha; Sipthorp, Mark; et al.
No abstract available